2011
DOI: 10.1128/jvi.00059-11
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Stimulates the Phosphatidylinositol 4-Kinase III Alpha-Dependent Phosphatidylinositol 4-Phosphate Production That Is Essential for Its Replication

Abstract: Phosphatidylinositol 4-kinase III alpha (PI4KA) is an essential cofactor of hepatitis C virus (HCV) replication. We initiated this study to determine whether HCV directly engages PI4KA to establish its replication. PI4KA kinase activity was found to be absolutely required for HCV replication using a small interfering RNA transcomplementation assay. Moreover, HCV infection or subgenomic HCV replicons produced a dramatic increase in phosphatidylinositol 4-phosphate (PI4P) accumulation throughout the cytoplasm, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
190
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(208 citation statements)
references
References 49 publications
17
190
1
Order By: Relevance
“…Both CypA and PI4KIII␣ are essential host cell factors for HCV replication. In case of the latter, kinase activity is enhanced upon HCV infection by interaction with NS5A and NS5B (63,64), resulting in increased PI4P levels. Although NS5A-PI4KIII␣ interaction occurs through NS5A domain I, it is also required for proper membranous web morphology, and therefore, we assessed the effect of I315G and P314A mutations on PI4KIII␣ activity by quantifying the intracellular PI4P levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both CypA and PI4KIII␣ are essential host cell factors for HCV replication. In case of the latter, kinase activity is enhanced upon HCV infection by interaction with NS5A and NS5B (63,64), resulting in increased PI4P levels. Although NS5A-PI4KIII␣ interaction occurs through NS5A domain I, it is also required for proper membranous web morphology, and therefore, we assessed the effect of I315G and P314A mutations on PI4KIII␣ activity by quantifying the intracellular PI4P levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to enteroviruses, the flavivirus Hepatitis C virus (HCV) requires PI4P lipids for replication, which are generated via the recruitment of PI4KIIIα [46][47][48][49][50][51][52][53]. West Nile virus attracts the cholesterol-synthesizing enzyme 3-HMGA-CoA reductase to replication sites [54,55], while dengue virus recruits fatty acid synthase and stimulates its activity [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…111 In hepatitis C virus-infected U2OS human osteosarcoma-derived cells, endogenous phosphatidylinositol 4-kinase-α was shown to act as a co-factor for hepatitis C virus RNA replication through generating PI(4)P at the endoplasmic reticulum of infected cells, which could recruit PI(4)P-binding proteins involved in viral replication. 112 Likewise, the coxsackievirus B3 was shown to utilize endogenous phosphatidylinositol 4-kinase-β in HeLa cells to generate an approximately five-fold increase in PI(4)P at enteroviral replication organelles. It was reported that the association of viral RNA polymerase with PI(4)P at the sites of phosphatidylinositol 4-kinase-β activity could facilitate viral replication.…”
Section: Pathogenic Entry Via the Host Extracellular Phospholipid Codementioning
confidence: 99%